Aspect of Uniqueness in Distinctiveness to the Development of Geotourism in Merek District - Habib Auliya, Muhammad; Ginting, Nurlisa; Zahrah, Wahyuni; KAHN, SABZALI MUSA (Talenta Publisher, 2025)
This study analyzes the uniqueness of geodiversity, ecology, and culture as the foundation for sustainable geotourism development in Brand District, Karo Regency. Using a mixed methods approach (questionnaire N=100, interview n=6, observation), the results showed that the uniqueness of Brand's geodiversity lies in the volcanic phenomena of the Toba Caldera such as Sipiso-piso Waterfall (120 m) and Bukit Gajah Bobok which are rich in potassium and magnesium minerals. MANOVA's analysis showed a significant difference in the perception of tourists and the public towards geological uniqueness (p<0.05). Ecologically, volcanic soils with low total dissolved solids (TDS) (<150 ppm) support organic agriculture, although they are threatened by land conversion (25% reduced agricultural land) and plastic waste (volume decreased by 30% through the waste bank program). Local cultures such as Ulos weaving and the Erpangir Ku Lau ritual are identity differentiators, but their marketing is limited locally without certification. The integration of all three aspects requires technological innovation (augmented reality for geological interpretation), diversification of cultural products (craft training), and data-driven spatial planning policies. Strategic recommendations include strengthening community participation through Pokdarwis, a circular economy through recycling waste into handicrafts, and multi-stakeholder collaboration to make Brand a model of sustainable geotourism in Indonesia. This research emphasizes that the synergy of technological innovation, active community participation, and holistic policies are the keys to the success of geotourism development.